Biological development of children and youth from pathological family conditions. I. Wards of part time care centers in Warsaw - Łaska-Mierzejewska, Teresa; Łuczak, Ewa (Anthropological Review, 1986)
The studies covered a total of 313 wards of Part Time Care Centers. This number comprised 227 boys and 86 girls in the age from 8 to 17 years. Anthropological examinations refered to measurements of body height and weight, the evaluation of secondary sexual traits in this age (the menarche in girls) and health conditions. Data concerning the above traits were also retrospectively obtained from the records since the time when the subjects were admitted to the institution. In 225 children of 313 additional measurements of 7 somatic traits were made and they are presented in fig. 3. Furhtermore exact information about the functioning of the family environment of the ward was collected. Due to a small number of the investigated subjects the results of somatic measurements were presented in the form of standardized values referring them to the arithmetical mean and the standard deviation of random sample of Warsaw children [J. CHARZEWSKI 1981]. This procedure permitted to omit the age groups of the examined subjects and to evaluate the differences in comparison with the reference group. The children from Part Time Care Centers show lower values of somatic traits and a slower rate of maturation in comparison with the random sample of Warsaw children. 1. The obtained differences are: - greater in boys than in girls - they are more intensively expressed in the height than in body weight. 2. These differences both in boys and girls decrease with the appearance of tfye successive degrees of sexual maturity being indirectly a proof of a delay in the maturity rate of the studied children. 3. The degree of the obtained differences depends on: - the extent of the pathology of family environment - and on the time of the child’s abiding in the Care Centers.